A novel guideline for the analysis of linear acceleration mechanics - outlining a conceptual framework of `shin roll` motion - Alt, T.; Oeppert, T. J.; Zedler, M.; Goldmann, J.-P.; Braunstein, B.; Willwacher, S. (Sports Biomechanics, 2023)
Linear acceleration is a key performance determinant and major training component of many sports. Although extensive research about lower limb kinetics and kinematics is available, consistent definitions of distinctive key body positions, the underlying mechanisms and their related movement strategies are lacking. The aim of this `Method and Theoretical Perspective` article is to introduce a conceptual framework which classifies the sagittal plane `shin roll` motion during accelerated sprinting. By emphasising the importance of the shin segment`s orientation in space, four distinctive key positions are presented (`shin block`, `touchdown`, `heel lock` and `propulsion pose`), which are linked by a progressive `shin roll` motion during swing-stance transition. The shin`s downward tilt is driven by three different movement strategies (`shin alignment`, `horizontal ankle rocker` and `shin drop`). The tilt`s optimal amount and timing will contribute to a mechanically efficient acceleration via timely staggered proximal-to-distal power output. Empirical data obtained from athletes of different performance levels and sporting backgrounds are required to verify the feasibility of this concept. The framework presented here should facilitate future biomechanical analyses and may enable coaches and practitioners to develop specific training programs and feedback strategies to provide athletes with a more efficient acceleration technique.